THE HISTORY OF THE EMERGENCE OF SOCIAL PROTECTION IN THE WORLD (Global Conference on Multidisciplinary Research and Innovation, 2026)
The history of social protection in the world reflects the gradual transformation of charity, religious assistance, communal solidarity, and state intervention into more organized systems of support for vulnerable groups. This article examines the emergence of social protection from early forms of mutual aid to modern state-centered welfare mechanisms. Particular attention is given to the twentieth century, when social protection became one of the key directions of public policy. Using the uploaded material, the article analyzes the Soviet experience after the October Revolution as an important historical stage in the institutionalization of social protection. The study shows that social protection developed unevenly across countries and epochs, but everywhere it was linked to social crises, wars, industrialization, and the need to stabilize society. The findings indicate that the emergence of modern social protection was conditioned not only by humanitarian ideas, but also by political struggle, economic transformation, and the state’s attempt to regulate labor, health, education, and basic welfare. The article concludes that social protection became a defining feature of modern governance precisely when support for the population moved from occasional assistance to systematic state responsibility.
Keywords: Social protection, social policy, welfare state, labor rights, public assistance, October Revolution, Soviet model, social history, world history, vulnerable groups.